ARTIFICIAL INTELLEGENCE AMD STUDENTS IN THE MODERN WORLD - Komilova Hilola (Western European Studies, 2024)
In this article, you will learn about "Artificial Intelligence", which has become a hot topic these days. In the article, what is artificial intelligence?, History of artificial intelligence, stages of development?, Is artificial intelligence dangerous to humanity? We will try to find answers to such questions. We will also learn the importance of artificial intelligence in the lives of young people.
Keywords: Artificial intelligence; mental ability; evolution; cryptographer